2003
DOI: 10.1136/jmg.40.7.526
|View full text |Cite
|
Sign up to set email alerts
|

Unusual cognitive and behavioural profile in a Williams syndrome patient with atypical 7q11.23 deletion

Abstract: C olorectal cancer (CRC) is the third most common cancer diagnosed in both men and women, and the second most common cause of cancer deaths in the United States. There were approximately 150 000 new cases resulting in 57 000 deaths in 2002.1 CRC is one of the most studied cancer types and its underlying aetiology best elucidated. Colorectal tumorigenesis involves a multistep process including genetic and epigenetic alterations of numerous CRC related genes that may act as either oncogenes or tumour suppressor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
1
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 20 publications
3
47
1
2
Order By: Relevance
“…ELN haploinsufficiency has been linked to supravalvular aortic and other stenoses (21,36,37), whereas a mouse model suggests that CYLN2 hemizygosity might contribute to the WBS cognitive profile (38). Furthermore, the study of WBS patients with atypical deletion suggests that GTF2IRD1, GTF2I and CYLN2 genes might contribute to the visual spatial processing deficits harbored by WBS patients (39,40). However, the gene(s) responsible for the IGT and silent diabetes reported in the majority of the WBS patients remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…ELN haploinsufficiency has been linked to supravalvular aortic and other stenoses (21,36,37), whereas a mouse model suggests that CYLN2 hemizygosity might contribute to the WBS cognitive profile (38). Furthermore, the study of WBS patients with atypical deletion suggests that GTF2IRD1, GTF2I and CYLN2 genes might contribute to the visual spatial processing deficits harbored by WBS patients (39,40). However, the gene(s) responsible for the IGT and silent diabetes reported in the majority of the WBS patients remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…However, the location of the breakpoints in nonhomologous or with low similarity sequences suggests that the most likely mechanism leading to this atypical rearrangements may be nonhomologous end joining or other processes that do not required high homology at the breakpoint, and support the proposal that other mechanisms predisposes to genomic instability of the WBS region 31 This study underscores the importance to map precisely the WBS deletion boundaries to revaluate the significance of the WBS genes hemizygosity in the pathogenesis of epilepsy, facial features, and neurological phenotypes. [32][33][34][35][36][37][38][39][40] CONFLICT OF INTEREST All patients and/or their parents gave written consent for the study, for genetic testing some gave consent for publication of photos. Ethics Committee approval was not required as this was not a specific study but a report of clinical investigation undertaken for four WBS patients, as part of their standard clinical care.…”
Section: Patient Wbs166mentioning
confidence: 99%
“…The detection of a normal full-scale IQ in our patient supports the previous assumptions that GTF2IRD1 and GTF2I genes are crucial for WBS cognitive features. 19,22,[27][28][29][30][31] Nevertheless, we have to emphasize that our patient exhibits a peculiar discrepancy between verbal IQ and performance IQ, resembling the PIQ/VIQ ratio that has been reported in typical WBS patients. 19,32,33 This finding seems contrary to previous reports of absent or minor visuospatial deficit in atypical WBS patients keeping GTF2IRD1 and GTF2I genes.…”
Section: Discussionmentioning
confidence: 65%
“…27 Other reports suggested that the GTF2I and GTF2IRD1 genes have dosagedependent influences on craniofacial and neurological development and that hemizygosity for these genes appears to be associated with the general intellectual disability/mental retardation 22 and/or visuospatial construction difficulties. 19,21,24,[28][29][30] Finally, further insights into genotype-phenotype correlations come from an intriguing report of an individual without the abnormal motor behavior and the specific spatial and impaired visual-spatial capacities. Genetic analysis showed that this patient had a deletion that excluded the genes RFC2, CLIP2, GTF2IRD1 and GTF2I.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation